2017
DOI: 10.1159/000479018
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Wearable Sensors in Parkinson and Huntington Disease Individuals: A Pilot Study in Clinic and at Home

Abstract: Background: Clinician rating scales and patient-reported outcomes are the principal means of assessing motor symptoms in Parkinson disease and Huntington disease. However, these assessments are subjective and generally limited to episodic in-person visits. Wearable sensors can objectively and continuously measure motor features and could be valuable in clinical research and care. Methods: We recruited participants with Parkinson disease, Huntington disease, and prodromal Huntington disease (individuals who car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,922 publications
(62 citation statements)
references
References 23 publications
0
62
0
Order By: Relevance
“…Earlier generations (BioStamp RC TM and investigational prototypes) of the technology have been used in academic research, including motor assessments in Parkinson disease [28], gait assessment in multiple sclerosis [13], posture classification in Huntington disease [12], postural sway in multiple sclerosis [29], and periodic leg movements in sleep (unpublished data). Additional independent research with BioStamp technology has looked at ambulatory vectorcardiography [30], spasticity [31], and more granular activities of daily living (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier generations (BioStamp RC TM and investigational prototypes) of the technology have been used in academic research, including motor assessments in Parkinson disease [28], gait assessment in multiple sclerosis [13], posture classification in Huntington disease [12], postural sway in multiple sclerosis [29], and periodic leg movements in sleep (unpublished data). Additional independent research with BioStamp technology has looked at ambulatory vectorcardiography [30], spasticity [31], and more granular activities of daily living (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Because of limited available technology, lack of validated digital endpoints, and financial drivers, clinicians still assess study participant status episodically, even during rigorous clinical trials. Unfortunately, these assessments are too often rater-dependent and are performed in an artificial environment [12]. Gathering objective, clinically meaningful data from the study participants in their own environment between clinic assessments, perhaps minimizing their frequency and intensity, represents one potential of cogently designed wearable devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than motor diagnosis as a singular endpoint, a composite of motor and cognitive functions and a comprehensive investigator assessment could provide a more robust and informative outcome measure. Wearable devices to quantitatively monitor movement may prove useful in improving the specificity and sensitivity of motor phenoconversion.…”
Section: Discussionmentioning
confidence: 99%
“…Among these novel measures are the time individuals spend lying down. In Huntington disease, a rare genetic disorder, Adams et al [3] found that ambulatory individuals with the condition who are well enough to come to the clinic spend half their days at home lying down, a previously unknown finding. In addition, digital biomarkers are not only measuring health but predicting it as well.…”
Section: Overviewmentioning
confidence: 99%